POLITIK HUKUM PENGUATAN DESENTRALISASI FISKAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DAERAH - agus darmawan (Universitas Lampung, 2014)
The study aims to find a legal political model the Indonesian government in the implementation of fiscal decentralization that is oriented towards improving the welfare of people in the area. Using normative approach can be concluded that the system updates the state financial management with the adoption of several laws in the management of state finances, among others, by arranging the principles of best (best practice) management of state finances, budgeting system and the structure of the budget, control range (span of control) financial administration, oversight and accountability mechanisms of state financial management, which is also applied in the area of financial management. However, developments in the field of state financial arrangements turned out to show a tendency towards recentralisation power system, at least in the areas of fiscal, necessitating the re-strengthening fiscal decentralization of financial management in order to achieve the welfare of all Indonesian people. Keywords: Politics Law, Fiscal Decentralization and Local Government